ALIH FUNGSI LAHAN HUTAN LINDUNG SEBAGAI TEMPAT PEMBUANGAN LIMBAH PERTAMBANGAN: PERSPEKTIF FUNGSI PERIZINAN SEBAGAI INSTRUMEN REKAYASA PEMBANGUNAN - Eduard Awang Maha Putra; Fathul Hamdani; Lalu Muhammad Azwar (Sabtida, 2024)
In August 2023, news circulated in one of the local mass media that PT Sumbawa Timur Mining proposed the use of 5,300 hectares of protected forest area in Dompu Regency, NTB to the NTB Provincial Government as a place for dumping tailings from mining, which then caused pros and cons. Through this research, the author aims to examine the regulation of the conversion of protected forest areas into mining areas in Indonesia and analyze the conversion of protected forest areas in Dompu Regency into dumping areas from the perspective of the licensing function as an instrument of development engineering. The method used in this research is normative legal research with statutory, conceptual and case approaches. The results show that the Forestry Law has opened up opportunities for the use of forest areas for development purposes outside of forestry activities in production forest areas and protected forest areas. Specifically, mining activities in protected forest areas are only allowed for mining activities carried out with a closed mining pattern. Meanwhile, tailings disposal can only be carried out in waste containment dams and sea facilities with certain specifications, so that tailings disposal cannot be disposed of carelessly in protected forest areas.